1978
DOI: 10.1159/000275386
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation and Its Mechanism of Cochlear Damage Resulting from Furosemide and Aminoglycoside Antibiotics

Abstract: The severe ototoxic interaction of the combined administration of furosemide and aminoglycoside antibiotics (kanamycin, streptomycin and gentamicin) was studied in rabbits, and its mechanism clarified. Severe damage occurred not only in the inner ear but also in the kidney when both furosemide and aminoglycoside antibiotics were administered to rabbits. Kanamycin concentration after a single injection of kanamycin with furosemide was much higher not only in the perilymph but also in the cerebrospinal fluid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The addition of a loop diuretic to an aminoglycoside administration has a more than additive ototoxic effect because diuretics facilitate aminoglycosides to pass the blood-cochlea barrier (3Y5); they allow aminoglycosides to more effectively spread through the cochlea by altering the endolymphatic potential (6,7), and they decrease the renal kanamycin clearance (8).…”
mentioning
confidence: 99%
“…The addition of a loop diuretic to an aminoglycoside administration has a more than additive ototoxic effect because diuretics facilitate aminoglycosides to pass the blood-cochlea barrier (3Y5); they allow aminoglycosides to more effectively spread through the cochlea by altering the endolymphatic potential (6,7), and they decrease the renal kanamycin clearance (8).…”
mentioning
confidence: 99%
“…This was the only patient we treated who developed sudden deafness and the only patient who received concurrent ethacrynic acid. DISCUSSION The data we 15 and 25%, respectively. Because these data were gathered in prospective, controlled, randomized, doubleblind trials, bias in assessing renal and auditory function was minimized.…”
Section: Methodsmentioning
confidence: 65%
“…A dose of 50 mg of furosemide per kg produced a minimal effect, whereas doses greater than 100 mg/kg produced severe irreversible decreases in cochlear potential. Obtani et al studied the interaction with kanamycin in rabbits given 30 mg offurosemide per kg for 5 to 60 days (15). All animals given the combination developed severe renal failure and severe loss of outer hair cells in the cochlea.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study (Ohtani et al, 1978) has shown severe damage not only of the inner ear but also of the kidneys following the administration of both FM and aminoglycoside antibiotics to rabbits. The present study was undertaken to assess the ototoxic effect of the combined administration of KM and BUN in comparison with that of the combined FM-KM administration, employing BUN doses as low as 1/40 to 1/60 of the dose of FM in the previous study, hence on a diuretically equipotent basis.…”
Section: Introductionmentioning
confidence: 94%